How can the Choice of Integration Method Optimize the Earthquake Finite Fault Simulation: A Case Study of 2004 Mw 6.1 Parkfield Earthquake - HoushmandViki, Ameneh; Ansari, Anooshiravan (Earth and Planetary Science, 2025)
Earthquake finite fault simulations confront time-consuming and complex calculations. Therefore, finding methods that result in rapid calculations generalized with sufficient accuracy is predominantly necessary. Different methods of finite fault surface integrals for the 2004 Mw 6.1 Parkfield earthquake have become the subject of the current study to achieve a fast and accurate calculation of earthquake finite fault simulation. Calculations are performed considering fault elements carried out with constant and variable source parameters, while interpolation functions can also be considered. The investigations implemented in this research show that changing the conventional trapezoidal integration method into Gaussian integration on optimal element size could reduce the estimated time of calculations. The surface integral can be done only on one Gaussian point, while the required time for calculations can decrease considerably. To simplify the complex structure of Green's function calculations, a constant Green's function can be assumed in a half-space, with a time shift corresponding to the arrival time of the fault rupture representing the Green's function for other sub-faults. ER